Ecology of Iron-Oxidizing Bacteria in Pyritic Materials Associated with Coal - Belly, R. T. (1974)
A technique was developed for measuring (14)CO(2) uptake by chemolithotrophic bacteria directly in pyritic materials associated with coal and coal refuse. There was good correlation between (14)CO(2) uptake, as determined by this technique, and the most probable number of iron-oxidizing bacteria. Maximal (14)CO(2) uptake occurred in coal refuse material 2 to 3 years old, and only slight incorporation was demonstrated in fresh material or material 40 years old. Samples taken from the surface of the coal refuse pile always demonstrated maximal (14)CO(2) uptake, and in most samples, only slight activity was demonstrated at depths below 8 to 10 cm. Optimal uptake of (14)CO(2) by natural samples occurred at 20 to 30 C and at a moisture content of between 23 and 35%. In addition to chemolithotrophic bacteria, heterotrophic fungi and yeasts were also routinely isolated in high numbers from acidic coal refuse. In contrast, acidophilic, heterotrophic bacteria were either absent or present in low numbers in such acidic samples.